The Urgence Of Counseling Guidance In Developing Student Discipline in Junior high school Muhammadiyah Tebing Tinggi - Daulay, Nurussakinah; Sumanti, Solihah Titin; Faisal, Faisal; Siregar, M Fajri Syahroni (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2021)
This study examines the urgency of counseling guidance in fostering student discipline at the Muhammadiyah Tebing Tinggi Private Junior High School. This research is based on the existence of student discipline problems at school. The disciplinary behavior is related to violations of the rules and regulations set by the school. Schools as a strategic place to overcome students' undisciplined approach require a counseling approach. This study aims to analyze the importance of counseling guidance in fostering student discipline. This study uses a qualitative method with a phenomenological approach. Data was collected by using observation techniques, in-depth interviews, and documentation studies. Research informants consisted of principals, BK teachers, and students. The results of this study indicate that the efforts made by schools in fostering student discipline are by providing counseling and punishment services. It is hoped that with these efforts, students will be able to behave in an orderly discipline, always in an orderly manner with regulations everywhere.